The coevolution of insect muscle TpnT and TpnI gene isoforms. - Herranz, R.; Mateos, J.; Mas, J.A.; Garcia-Zaragoza, E.; Cervera, M.; Marco, R. (Molecular Biology and Evolution, 2005)
In bilaterians, the main regulator of muscle contraction is the troponin (Tpn) complex, comprising three closely interacting subunits (C, T, and I). To understand how evolutionary forces drive molecular change in protein complexes, we have compared the gene structures and expression patterns of Tpn genes in insects. In this class, while TpnC is encoded by multiple genes, TpnT and TpnI are encoded by single genes. Their isoform expression pattern is highly conserved within the Drosophilidae, and single orthologous genes were identified in the sequenced genomes of Drosophila pseudoobscura, Anopheles gambiae, and Apis mellifera. Apis expression patterns also support the equivalence of their exon organization throughout holometabolous insects. All TpnT genes include a previously unidentified indirect flight muscle (IFM)-specific exon (10A) that has evolved an expression pattern similar to that of exon 9 in TpnI. Thus, expression patterns, sequence evolution trends, and structural data indicate that Tpn genes and their isoforms have coevolved, building species- and muscle-specific troponin complexes. Furthermore, a clear case can be made for independent evolution of the IFM-specific isoforms containing alanine/proline-rich sequences. Dipteran genomes contain one tropomyosin gene that encodes one or two high-molecular weight isoforms (TmH) incorporating APPAEGA-rich sequences, specifically expressed in IFM. Corresponding exons do not exist in the Apis tropomyosin gene, but equivalent sequences occur in a high-molecular weight Apis IFM-specific TpnI isoform (TnH). Overall, our approach to comparatively analyze supramolecular complexes reveals coevolutionary trends not only in gene families but in isoforms generated by alternative splicing.